The perception of nurses concerning computerised handover and its influence on the quality of patient care - Lee, Khuan; Juni, Muhamad Hanafiah (Community Health Society Malaysia (CHSM), 2016)
Background: Nursing handover communications play an important role in ensuring the quality of care of patients.